Exhumation history and landscape evolution of the Sierra de San Luis (Sierras Pampeanas, Argentina)-new insights from low-temperature thermochronological data - Bense, Frithjof (2017)
This paper presents low-temperature thermochronological data and K--Ar fault gouge ages from the Sierra de San Luis in the Eastern Sierras Pampeanas in order to constrain its low-temperature thermal evolution and exhumation history. Thermal modelling based on (U-Th)/He dating of apatite and zircon and apatite fission track dating point to the Middle Permian and the Triassic/Early Jurassic as main cooling/exhumation phases, equivalent to ca. 40-50% of the total exhumation recorded by the applied methods. Cooling rates are generally low to moderate, varying between 2-10 °C/Ma during the Permian and Triassic periods and 0.5-1.5 °C/Ma in post-Triassic times. Slow cooling and, thus, persistent residence of samples in partial retention/partial annealing temperature conditions strongly influenced obtained ages. Thermochronological data indicate no significant exhumation after Cretaceous times, suggesting that sampled rocks were already at or near surface by the Cretaceous or even before. As consequence, Cenozoic cooling rates are low, generally between 0.2-0.5 °C/Ma which is, depending on geothermal gradient used for calculation, equivalent to a total Cenozoic exhumation of 0.6-1.8 km. K-Ar fault gouge data reveal long-term brittle fault activity. Fault gouge ages constrain the end of ductile and onset of brittle deformation in the Sierra de San Luis to the Late Carboniferous/Early Permian. Youngest K-Ar illite ages of 222-172 Ma are interpreted to represent the last illite formation event, although fault activity is recorded up to the Holocene.